Two Dimensional Ultrasonographic Analysis of Placental Maturity and Its Correlation to Gestational Age and Maternal Parameters - Mumal Nagwani Mishra (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
Background: As a foetal organ, the placenta is subjected to the same stress and strain as the foetus. As a result, any disease process that affects the mother or foetus has a significant impact on the placenta. The current study sought to ascertain the changes and growth of the placenta as the fetus’s age advances during the third trimester of pregnancy. The relationship between maternal variables (maternal age and parity) and placental maturity werealso studied. Methods: The study involved 100 women in their third trimester of pregnancy who visited the antenatal clinic of Obstetrics and Gynecology at Queen Mary’s Hospital, King George’s Medical University, Lucknow. Any cases with obstetrical, gynaecological, medical, or surgical disorders were ruled out. The placenta’s maturity grade was assessed. Results: The frequencies of grade 0, grade I, grade II and grade III placental maturity were 1%, 6%, 46% and 47% respectively. Conclusion: Since p-value was high, there was a significant variation in placental maturity grade among different gestational groups.